A study on promotional strategies of Sarakoppes Sdn. Bhd. / Salmah Mat - Mat, Salmah (2002)
The purpose of the study is to analyze the implementation of promotion strategies and to seek out the most appropriate suggestions and recommendations in order to improve the existing promotion strategy of the company. The level of respondent’s perception, experience and expectation were measured, to enhance the promotion strategies. Throughout the period of this study, one hundred and fifty-five (155) responses had been received and the data collected was analyzed. Promotion is one of the four major elements of the company’s marketing mix . The result shows that the company has carried out some promotion strategies in their business to inform the public about their business.